Understanding reasons for asthma outpatient (non)-attendance and exploring the role of telephone and e-consulting in facilitating access to care: exploratory qualitative study. Issue 3 (2nd June 2006) - van Baar, J D; Joosten, H; Car, J; Freeman, G K; Partridge, M R; van Weel, C; Sheikh, A
Abstract : Objective: To understand factors influencing patients' decisions to attend for outpatient follow up consultations for asthma and to explore patients' attitudes to telephone and email consultations in facilitating access to asthma care. Design: Exploratory qualitative study using in depth interviews. Setting: Hospital outpatient clinic in West London. Participants: Nineteen patients with moderate to severe asthma (12 "attenders" and 7 "non-attenders"). Results: Patients' main reasons for attending were the wish to improve control over asthma symptoms and a concern not to jeopardise the valued relationship with their doctor. Memory lapses, poor health, and disillusionment with the structure of outpatient care were important factors implicated in non-attendance. The patients were generally sceptical about the suggestion that greater opportunity for telephone consulting might improve access to care. They expressed concerns about the difficulties in effectively communicating through non-face to face media and were worried that clinicians would not be in a position to perform an adequate physical examination over the telephone. Email and text messaging were viewed as potentially useful for sending appointment reminders and sharing clinical information but were not considered to be acceptable alternatives to the face to face clinic encounter. Conclusions: Memory lapses, impaired mobility due to poor health, and frustration with outpatient clinic organisation resulting in long waiting times and discontinuity of care are factors that deter patients from attending for hospital asthma assessments. The idea of telephone review assessments was viewed with scepticism by most study subjects. Particular attention should be given to explaining to patients the benefits of telephone consultations, and to seeking their views as to whether they would like to try them out before replacing face to face consultations with them. Email and text messaging may have a role in issuing reminders about imminent appointments.